THE LEGAL FRAMEWORK FOR ISLAMIC BANKING AND THE QUEST FOR FINANCIAL INCLUSION IN NIGERIA - Bebeji, Umar Sani; Bala, Hussaini; Bala, Hassan (Jurnal Syariah, 2020)
The banking sector is the backbone of every economy. It determines not only the pace of growth of modern economic systems, but also the prosperity of nations. But its reliance on interest, liberal prudential guidelines and its very capitalist foundation make it incompatible with Islamic law – the faith practiced predominantly in some regions of Nigeria. Securing loans for investments comes with cut-throat conditions, riddled with cases of fraudulent and unfair practices. As a way around this, scholars began to think of how to expurgate those elements considered incompatible with the Shariah. Since the enactment of the Banks and Other Financial Institution’s Decree in 1991, which vaguely introduced the profit loss sharing principle of banking, nothing tangible was done to give effect to the provisions until 2011 when the Non-Interest Financial (NIFI) Services Guidelines was issued by the CBN. As a result of this development Jaiz Bank PLC was granted a license as a regional full-fledged Islamic bank, which metamorphosed into a national bank. This, however, was not without resistance as manifested in a suit against the CBN for issuing the guidelines. The paper, thus, attempts an analysis of the legal framework and how it can push up financial inclusion in Nigeria, adopting the doctrinal methodology approach to examine legislation, case-law and existing literature. It highlights some of the approaches of the Central Bank of Nigeria (CBN) and efforts to make the legal and institutional framework favourable for Islamic banking to thrive so that the substantial Muslim population can be brought into the formal financial stream to access funds for investments without upsetting the fundamental teachings of Islam. It further argues that that there is a strong correlation between the inadequacy of legal support for Islamic banking and high rate of financial exclusion particularly in the Muslim-dominated communities. Similarly, it reveals that there is not a shred of rational basis for the opposition to Islamic banking in Nigeria as it does not seek to foster any sinister agenda of “Islamising” the polity. As Nigeria is trying to push for more financial inclusion, Islamic banking can help improve existing credit delivery mechanisms for effective outreach to the teeming excluded population of Muslims. It, therefore, strongly recommends that a comprehensive legislation be enacted by the National Assembly (NASS) of Nigeria to support the prospects of this novel and popular banking model and also help promote and protect investments in the area. This will shove off financial inclusion in many ways.